2023
DOI: 10.1021/acs.langmuir.3c02031
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bi2O3/Bismuth Titanates Modified with Metal–Organic Framework-In2S3/CdIn2S4 Materials for Electrocatalytic H2 Production and Its Photoactivity

Krishnakumar Balu,
Balakrishna Avula,
Mani Durai
et al.

Abstract: Compositional and structural elucidation of the materials is important to know their properties, chemical stability, and electro-photoactivity. The heterojunction electrocatalyst and photocatalyst activity could open a new window for solving the most urgent environmental and energy problems. Here, for the first time, we have designed and fabricated Bi 2 O 3 /bismuth titanates modified with MOF-In 2 S 3 /CdIn 2 S 4 materials by a stepwise process. The detailed structural elucidation and formation of mixed compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Among these, β-In 2 S 3 is known to be the most stable structural form at room temperature, and it is a defect spinel structure that displays intriguing physical properties due to cation vacancies creating intermediate band or trapping levels within the bandgap. 15,16 Li et al studied the electronic structure of the Eu-doped In 2 S 3 system by density functional theory calculations, finding that the introduction of Eu doping and In vacancies induces impurity energy levels, leading to ferromagnetic behavior. 17 Datta et al observed octet paramagnetic bands in Co-doped In 2 S 3 micropompons through EPR spectra analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, β-In 2 S 3 is known to be the most stable structural form at room temperature, and it is a defect spinel structure that displays intriguing physical properties due to cation vacancies creating intermediate band or trapping levels within the bandgap. 15,16 Li et al studied the electronic structure of the Eu-doped In 2 S 3 system by density functional theory calculations, finding that the introduction of Eu doping and In vacancies induces impurity energy levels, leading to ferromagnetic behavior. 17 Datta et al observed octet paramagnetic bands in Co-doped In 2 S 3 micropompons through EPR spectra analysis.…”
Section: Introductionmentioning
confidence: 99%